Inside Front Cover: Multispectral optoacoustic tomography of systemic sclerosis (J. Biophotonics 11/2018). Issue 11 (9th November 2018) - Masthoff, Max; Helfen, Anne; Claussen, Jing; Roll, Wolfgang; Karlas, Angelos; Becker, Heidemarie; Gabriëls, Gert; Riess, Jan; Heindel, Walter; Schäfers, Michael; Ntziachristos, Vasilis; Eisenblätter, Michel; et al.
Abstract : Hybridized Multispectral Optoacoustic Tomography/Ultrasonography reveals dedicated biomarkers in inflamed joints in systemic sclerosis. Further details can be found in the article by Max Masthoff, Anne Helfen, Jing Claussen, et al. (e201800155 ). Abstract : Hybridized Multispectral Optoacoustic Tomography/Ultrasonography reveals dedicated biomarkers in inflamed joints in systemic sclerosis. Further details can be found in the article by Max Masthoff, Anne Helfen, Jing Claussen, et al. (e201800155 ).